Older people – nursing home care – qualitative research - Brown, Laura (2010)
Abstract Background: Dementia is a topic of interest for me and with the recent launch of the National Dementia Strategy it is timely to investigate. There is increasing concern that older people are discriminated against in terms of access to services and those with dementia are among the most vulnerable of patient groups. The recent strategy calls for greater awareness of dementia among health care workers. Aim: To examine the level of dementia knowledge and attitudes towards ageing and to test whether there is an association between them among student nurses. Research Design: Questionnaire survey of student nurses. Methods: A self-completion questionnaire was distributed to pre-registration student nurses. The questionnaire measured knowledge of dementia on a scale of 0 to 24 with higher scores indicating greater knowledge. Attitudes to ageing were measured with the AGED Inventory. The two variables were examined for differences on demographic and course related variables. The two score variables were then analysed to assess whether there was a relationship between the two. Results: With regards to dementia, a mean total score of 14.2 indicated an average achievement of 60%. Public health issues such as mortality, prevalence and cost were answered poorly. The existence of negative attitudes towards older people were found among student nurses, especially with regards to adventurousness and sexuality. No direct relationship between dementia knowledge and attitudes towards ageing was found. Pearson’s correlation coefficient was 0.041 (P=0.39) suggesting no evidence for a linear relationship. Conclusions: As a result of an ageing population, the burden dementia presents is likely to increase and as a result, it is crucial that current student nurses are prepared in order to deal with this challenge once qualified. Findings from this study would suggest that this is not the case. Pre-registration nurses would therefore benefit from increased education in both dementia and challenging stereotypes.